Synbiotics Containing Nanoprebiotics: A Novel Therapeutic Strategy to Restore Gut Dysbiosis - Hong, Liang; Lee, Sang-Mok; Kim, Whee-Soo; Choi, Yun-Jaie; Oh, Seo-Ho; Li, Yu-Ling; Choi, Seung-Hoon; Chung, Dong Hyen; Jung, Eunkyoung; Kang, Sang-Kee; Cho, Chong-Su (Frontiers in Microbiology, 2021)
A new formulation, nanoprebiotics [e.g., phthalyl pullulan nanoparticles (PPNs)], was demonstrated to enhance the antimicrobial activity of probiotics [e.g., Lactobacillus plantarum (LP)] in vitro through intracellular stimulation better than that by backbone prebiotics, which are commonly used. In this study, we aimed to investigate whether this combination would exert distinct effects as synbiotics in vivo. Synbiotics combinations of LP, pullulan, and PPNs were used as experimental treatments in a dysbiosis-induced murine model and their restorative effect was assessed using pathogen Escherichia coli K99 challenge. Our results showed that the E. coli infection was suppressed markedly in the experimental group fed with synbiotics containing PPNs. In addition, the decrease in serum endotoxin level after synbiotics treatment suggested the reinforcement of the gut barrier. Comparison of treatment groups, including a normal control group, showed that synbiotics containing PPNs increased microbial diversity which is a representative parameter of healthy status. Furthermore, distinct from probiotics treatment alone, synbiotics showed additive effects of enrichment of several well-known beneficial bacteria such as Lactobacillus, Bifidobacterium, and other butyrate-producing bacteria including Faecalibacterium. Collectively, our results indicate that synbiotics containing PPNs are very effective at restoring gut dysbiosis, suppressing pathogenic infection, and increasing microbial diversity, suggesting that synbiotics with nanoprebiotics have the potential to be a novel strategy for ameliorating gut dysbiosis and infectious diseases.